Imajinasi Masa Kecil di Desa sebagai Sumber Ide dalam Penciptaan Karya Seni Lukis - Masruri, Shubhan; Gozali, Amir (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2023)
The background of the creation of this Final Project painting inspired by childhood imagination in the village is the author's experience in viewing events and events that are being carried out by small children in the present that have similarities with the memories that the little writer had made as a village child who was full of imagination. The creation of this painting is structured as a form of expression of the author's longing for childhood memories that are impossible to repeat. The technique used in the creation of works is the placard technique, using acrylic paint on canvas. The creation of works refers to the theory put forward by L.H. Chapman. First, the effort to find ideas, the second is the stage of refining, developing, and solidifying the initial idea, and the third is the visualization stage in the media. The results obtained from the creation of works of art are paintings inspired by childhood imaginations in the village. In addition, the experience in creating this painting is expected to provide positive value for oneself and others.